IMPROVEMENT OF THE MECHANISM OF VALUE ADDED TAX IN THE SYSTEM OF INDIRECT TAXES - Gafforov Shukhrat Nasrievich (Journals Park Publishing, 2023)
The article is devoted to the consideration of the issues of improving the administration of value added tax as a result of tax reforms implemented in our country. In reliance upon the research results relevant proposals have been made to simplify the administration of value added tax.
Keywords: tax, value added tax, tax administration, tax rate.